1997
DOI: 10.1046/j.1365-2958.1997.5951971.x
|View full text |Cite
|
Sign up to set email alerts
|

FIS modulates growth phase‐dependent topological transitions of DNA in Escherichia coli

Abstract: SummaryThe Escherichia coli DNA-binding protein FIS serves as a DNA architectural factor in two unrelated enzymatic reactions, the site-specific inversion of DNA and transcriptional activation of stable RNA promoters. In both these processes, FIS facilitates the assembly and dynamic transitions of two structurally distinct nucleoprotein complexes. We have proposed previously that, in these systems, FIS stabilizes writhed DNA microloops by binding at multiple helically phased sites in DNA. However, FIS also bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 76 publications
6
104
1
Order By: Relevance
“…Johnson and colleagues also did not observe altered levels of supercoiling in strains lacking fis (28; R. Johnson, personal communication). These results conflict with results in a previous report in which it was concluded that plasmids are hypersupercoiled in ⌬fis strains (38). We do not know the basis for this discrepancy.…”
Section: Vol 185 2003 Intp and Ppgpp In Feedback Control Of Rrna Sycontrasting
confidence: 57%
“…Johnson and colleagues also did not observe altered levels of supercoiling in strains lacking fis (28; R. Johnson, personal communication). These results conflict with results in a previous report in which it was concluded that plasmids are hypersupercoiled in ⌬fis strains (38). We do not know the basis for this discrepancy.…”
Section: Vol 185 2003 Intp and Ppgpp In Feedback Control Of Rrna Sycontrasting
confidence: 57%
“…The existence of local gradients of superhelical density in the vicinity of DNA translocases implies that, as the DNA superhelical density varies over a wide range, the nature of the unconstrained superhelicity-the twist-writhe partition-must also vary, with writhe favored at the lower densities. However, in principle, proteins that constrain negative superhelicity might be expected to bind preferentially to DNA within a narrow range of superhelical density, as has been shown for the FIS protein, which favors a low negative superhelical density (Schneider et al 1997). There is unfortunately little information available for other proteins, but another possible example would be the eukaryotic HMG domain, which, in addition to being the principal component of the small HMGB proteins (Thomas and Travers 2001), is found in certain subunits of chromatin remodeling complexes (Quinn et al 1996) and of transcription elongation complexes (Orphanides et al 1999;Brewster et al 2001;Formosa et al 2001;Mason and Struhl 2003).…”
Section: Gradients Of Superhelicity and Protein Bindingmentioning
confidence: 95%
“…It was shown that FIS preferentially binds the supercoiled DNA from the intermediate fraction and much less so from the extremes of the topological spectrum (Schneider et al 1997). This preference is associated with geometrical constraints imposed by local DNA geometry on the binding of closely spaced helix-turn-helix DNAbinding motifs of FIS (Stella et al 2010), such that the FIS molecule can be conceived as a wedge fixing a particular DNA geometry in which the two adjacent major groves are in close proximity.…”
Section: Fis-rna Polymerase Complexmentioning
confidence: 99%
“…With increasing concentrations, Fis interacts with an increasing number of weaker DNA sites until binding becomes nonspecific (8,67). However, distinctions between specific Fis-DNA interactions of various strengths and truly nonspecific interactions (i.e., interactions at random sites) have seemed vague.…”
Section: Specificity Of Bindingmentioning
confidence: 99%
“…The impact of Fis on cell physiology is widespread. As a nucleoid-associated protein, it is able to interact with a large number of DNA sites to alter DNA topology (66,67). Numerous genes are subject to positive or negative regulation by Fis directly or indirectly (6,10,19,22,30,49,56,61,(73)(74)(75).…”
mentioning
confidence: 99%